2017
DOI: 10.1111/asj.12837
|View full text |Cite
|
Sign up to set email alerts
|

Delicate changes of bioapatite mineral in pig femur with addition of dietary xylooligosaccharide: Evidences from Raman spectroscopy and ICP

Abstract: Bone mineral is strongly correlated with performance and health of animal bodies. The mineral bioapatite (BAp) is the dominant component in bone tissue. This study investigated mineralogical changes of BAp in pig femur by Raman spectroscopy and inductively coupled plasma optical emission spectrometry (ICP-OES). The pigs had been raised with various xylooligosaccharide (XOS) additions at two stages of growth (growing and fattening periods). The results show that XOS can decrease the degree of carbonate substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
(95 reference statements)
1
12
0
Order By: Relevance
“…The changes of crystallinity or hydroxyapatite crystal domain size influence bone mechanical properties [35, 51, 52]. There are also some recent studies showing that dietary additives can influence bone crystals structure in pigs [53] or rats [22]. As shown by FT-IR and XRD analyses (Fig 3, Table 3) no differences in the degree of mineralization or hydroxyapatite crystallites structure were observed in our study.…”
Section: Discussionsupporting
confidence: 55%
“…The changes of crystallinity or hydroxyapatite crystal domain size influence bone mechanical properties [35, 51, 52]. There are also some recent studies showing that dietary additives can influence bone crystals structure in pigs [53] or rats [22]. As shown by FT-IR and XRD analyses (Fig 3, Table 3) no differences in the degree of mineralization or hydroxyapatite crystallites structure were observed in our study.…”
Section: Discussionsupporting
confidence: 55%
“…In comparison to other prebiotic oligosaccharides, XOS resulted in greater colonic total wet weight but had no effect on colon wall weight [ 68 ]. Interestingly, a very recent investigation of dietary XOS on bone mineral crystallinity in swine femurs suggests that XOS increases the crystallinity of bone and that the influence of XOS on bone may be more prevalent during periods of growth, as the effects were not seen in bones collected during later stages of life [ 69 ].…”
Section: Prebioticsmentioning
confidence: 99%
“…Similar to the breaking strength, femoral mineral crystallinity benefitted most in 4% XOS group. Moreover, it was not unexpected that the studied bone parameters enhanced significantly in the period of later growth because of the longer duration of administration [17].…”
Section: Discussionmentioning
confidence: 88%
“…One of these studies reported that the probiotics L. paracasei HII01, XOS, or both together as a biotic therapy produced similar potential enhancement of bone microarchitecture in rats fed a high-fat diet (HFD), possibly by mitigating osteoclast-mediated bone resorption and promoting osteoblast-induced bone formation [16]. In addition, previous research into dietary XOS on bone mineral crystallinity in swine femurs suggested that XOS enhances the crystallinity of bone and that the effects of XOS on femurs may be more obvious during periods of early growth, while this influence was not observed in bones sampled during later growth [17]. These studies suggest that XOS may be involved in the absorption of minerals and improving bone health.…”
Section: Introductionmentioning
confidence: 99%